Comparing school students’ written productions: modal alternation in texts by Italian and Ticino student - Eleonora Zucchini (Italiano a scuola)
This paper aims to investigate the phenomenon of alternation between indicative and subjunctive in complement clauses in texts written by students from Italian and the Canton Ticino (Switzerland). Italian speakers within Italy’s national borders show a strong awareness of the importance of correctly using subjunctive. Therefore, it is worth investigating whether the same holds true for Italian speakers in Switzerland as well. This study will show that the two populations show minor but significant differences in mood selection.